2023
DOI: 10.1038/s41598-023-41081-w
|View full text |Cite
|
Sign up to set email alerts
|

Early elevation of high-sensitivity C-reactive protein as a predictor for cardiovascular disease incidence and all-cause mortality: a landmark analysis

Hye Sun Lee,
Jun-Hyuk Lee

Abstract: We investigated the association between early elevation of high-sensitivity C-reactive protein (hsCRP) and cardiovascular disease (CVD) incidence, all-cause mortality, and CVD mortality. We analyzed 6567 participants from the Korean Genome and Epidemiology Study_Ansan_Ansung cohort between 2005 and 2018. The Kaplan–Meier curves and modified Cox regression by Fine and Gray were used to estimate hazard ratios (HRs) with 95% confidence intervals (CIs) for CVD incidence, all-cause mortality, CVD mortality, cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Chronic subclinical inflammation is another potential factor implicated in the association between higher proNT levels and cardiovascular organ damage. In line with prior studies showing the pro-inflammatory properties of NT, we observed that subjects with higher proNT levels displayed increased levels of the pro-inflammatory marker hsCRP, a broadly recognized predictor of CVDs 48 . However, we found that the association between higher levels of proNT and vascular damage was independent of hsCRP values, but given the complexity and redundancy of inflammatory pathways involved in the development of atherosclerosis 49 , the role of other pro-inflammatory factors in mediating the negative effect of proNT on vascular biology may not be firmly excluded.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic subclinical inflammation is another potential factor implicated in the association between higher proNT levels and cardiovascular organ damage. In line with prior studies showing the pro-inflammatory properties of NT, we observed that subjects with higher proNT levels displayed increased levels of the pro-inflammatory marker hsCRP, a broadly recognized predictor of CVDs 48 . However, we found that the association between higher levels of proNT and vascular damage was independent of hsCRP values, but given the complexity and redundancy of inflammatory pathways involved in the development of atherosclerosis 49 , the role of other pro-inflammatory factors in mediating the negative effect of proNT on vascular biology may not be firmly excluded.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, most blood biomarkers measured are known to capture relatively acute dietary effects, meaning that with the present measurements we are underpowered to detect likely long-term effects of periodic restriction of animal products on markers of human health. Another limitation of our study is that we report on levels of inflammation through quantification of CRP levels instead of high-sensitivity CRP (hs-CRP), which is more commonly used to detect the risk for inflammatory conditions 35 . Finally, although we have adjusted for confounding factors to the best of our ability, some residual effects may persist in reported results.…”
Section: Discussionmentioning
confidence: 99%